Об оптимальном восстановлении значений операторов - Корнейчук, Н.П. (Український математичний журнал, 1994)
For a continuous operator А:X→Y, we formulate the problem of the optimal renewal of values Аx, x ∈ X by decreasing the uncertainty domain by using an information μk(x),k=1,2,..., where μk are continuous functionals, defined on the space X. Specific results are obtained for some integral operators in functional spaces.